Science, Translation and the Mangle: A Performative Conceptualization of Scientific Translation - Olohan, Maeve (Meta, 2016)
Against a backdrop of growing interest in historical and sociological approaches to the translation of science, this paper explores the conceptual potential of Andrew Pickering’s ‘mangle of practice’ (Pickering 1992; 1993; 1995; Pickering and Guzik 2008) as a sociological framework for research into the translation of science. Pickering’s approach is situated within a performative idiom of science and seeks to account for the interplay of material and human agency in scientific practice. It sees scientific and technological advances as emerging temporally from a dialectic of resistance and accommodation, metaphorically the mangle of practice. This paper introduces the main tenets of Pickering’s argument, contextualizing it within the field of science and technology studies. It then explores some of the implications of construing translation in these terms. Firstly, this conceptual approach helps to recognize the role of translation in the performance of science and to seek ways of studying translation practices as an integral component of scientific practices. Secondly, Pickering’s posthumanist or decentred perspective focuses on both material and human agency and the interplay between them; a similar approach to the study of translation would foreground the interaction between translator agency and material performativity in studies of translation practices. I conclude with proposals for adopting this ontological shift in translation studies, where it may have the potential to enhance our understanding of translation practices, in particular in relation to tools, technologies and sociotechnical developments in translation.